High Serum Procalcitonin Concentrations in Patients With Hemorrhagic Fever With Renal Syndrome Caused by Hantaan Virus - Fan, Xiude; Deng, Huan; Sang, Jiao; Li, Na; Zhang, Xiaoge; Han, Qunying; Liu, Zhengwen (Frontiers in Cellular and Infection Microbiology, 2018)
Objective: This study analysed the significance of procalcitonin (PCT) in patients with haemorrhagic fever with renal syndrome (HFRS) caused by Hantaan virus. Methods: The demographics and clinical and laboratory data including PCT at hospital admission in 146 adults with HFRS were retrospectively analysed. Results: PCT level was significantly higher in severe patients (n=72) than in mild patients (n=74, p<0.001) and independently associated with disease severity (OR 1.082, 95% CI 1.014-1.155, p=0.017). PCT had an area under the receiver operating characteristic curve (AUC) value of 0.738 (95% CI 0.657-0.820, p<0.001) for predicting severity. PCT level was significantly increased in patients with bacterial infection (n=87) compared with those without (n=59, p=0.037) and associated with bacterial infection (OR 1.685, 95% CI 1.026-2.768, p=0.039). The AUC value of PCT for predicting bacterial infection was 0.618 (95% CI 0.524-0.711, p=0.016). PCT level was significantly elevated in non-survivors (n=13) compared with survivors (n=133, p<0.001) and independently associated with mortality (OR 1.075, 95% CI 1.003-1.152, p=0.041). The AUC value of PCT for predicting mortality was 0.819 (95% CI 0.724-0.914, p<0.001). Conclusion: PCT concentrations at admission would be predictive of disease severity, secondary bacterial infection and mortality in patients with HFRS caused by Hantaan virus.